Motor Variability during Sustained Contractions Increases with Cognitive Demand in Older Adults - Vanden Noven, Marnie L.; Pereira, Hugo M.; Yoon, Tejin; Stevens, Alyssa A.; Nielson, Kristy A.; Hunter, Sandra K. (Frontiers in Aging Neuroscience, 2014)
To expose cortical involvement in age-related changes in motor performance, we compared steadiness (force fluctuations) and fatigability of submaximal isometric contractions with the ankle dorsiflexor muscles in older and young adults and with varying levels of cognitive demand imposed. Sixteen young (20.4 ± 2.1 year: 8 men, 9 women) and 17 older adults (68.8 ± 4.4 years: 9 men, 8 women) attended three sessions and performed a 40 s isometric contraction at 5% maximal voluntary contraction (MVC) force followed by an isometric contraction at 30% MVC until task failure. The cognitive demand required during the submaximal contractions in each session differed as follows: (1) high-cognitive demand session where difficult mental math was imposed (counting backward by 13 from a 4-digit number); (2) low-cognitive demand session which involved simple mental math (counting backward by 1); and (3) control session with no mental math. Anxiety was elevated during the high-cognitive demand session compared with other sessions for both age groups but more so for the older adults than young adults (p < 0.05). Older adults had larger force fluctuations than young adults during: (1) the 5% MVC task as cognitive demand increased (p = 0.007), and (2) the fatiguing contraction for all sessions (p = 0.002). Time to task failure did not differ between sessions or age groups (p > 0.05), but the variability between sessions (standard deviation of three sessions) was greater for older adults than young (2.02 ± 1.05 vs. 1.25 ± 0.51 min, p < 0.05). Thus, variability in lower limb motor performance for low- and moderate-force isometric tasks increased with age and was exacerbated when cognitive demand was imposed, and may be related to modulation of synergist and antagonist muscles and an altered neural strategy with age originating from central sources. These data have significant implications for cognitively demanding low-force motor tasks that are relevant to functional and ergonomic in an aging workforce.